PENGARUH PEMBERIAN AROMA TERAPI LAVENDER TERHADAP TINGKAT KECEMASAN CALON AKSEPTOR KB IUD DI KLINIK SYAHBI MEDITRA DI DESA BODANG KECAMATAN PADANG KABUPATEN LUMAJANG - Rosalina, Reny; Alfitri, Rosyidah; Keswara, Nila Widya (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The Maternal Mortality Rate (MMR) in Indonesia has not improved significantly from year to year. One way to reduce MMR is by using contraception. From brief interviews with 16 potential acceptors at the Syahbi Meditra clinic, some mothers said that they felt afraid and anxious about changing their family planning method to an IUD/implant method. Many factors influence the lack of IUD use, one of which is fear and anxiety among potential acceptors about installing the contraceptive device. The aim of this research was to determine the effect of providing lavender aromatherapy on the anxiety level of prospective IUD contraceptive acceptors. This research used a pre-experimental design with a one group pre-post test design method with a population of 16 potential IU family planning acceptors and a sample of 16 respondents using a total sampling technique. Data collection includes coding, editing and tabulating. Then the data was analyzed computer using the Paired Samples Test (asymp. Sig 2-tailed) p-value = 0.000 < 0.05. So Ha is accepted, namely that there is an effect of giving Lavender Aromatherapy on the Anxiety Level of Prospective IUD KB Acceptors. The conclusion of this research is that there is an effect of giving Lavender Aromatherapy on the Anxiety Level of Prospective IUD KB Acceptors. The suggestion is that the research site should be able to make innovations related to reducing the anxiety level of prospective IUD acceptors with complementary therapies